QUALITY OF HOME STAY SERVICES TOWARDS GUEST’S SATISFACTION IN KALIBUKBUK VILLAGE AT BULELENG REGENCY - Ni Desak Made Santi Diwyarthi; I Nyoman GD Mas Wiartha; Putu Diah Prabawati (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2019)
This study aims to identify data relating to the Quality of Home Stay Services towards Guest’s Satisfaction in Kalibukbuk Village, Buleleng Regency, Bali. The sample collection method used ispurposive random sampling, with totally of 103 respondents. Data collection techniques used are interviews, observation, documentation and questionnaires with Likert scale. The data analysis technique used is Structural Equation Model (SEM).There are five aspects measured, including Physical Form, Reliability, Responsiveness, Assurance, and Empathy in the quality of homestay services that affect guest satisfaction in Kalibukbuk Village at Buleleng Regency. The results showed that service quality variables consisting of physical form, reliability, responsiveness, assurance, and empathy simultaneously had an influence on guest satisfaction in quality of homestay services. Service quality variables consist of physical form, reliability, responsiveness, assurance, empathy partially have positive and significant effect on guest satisfaction in quality of homestay services in Kalibukbuk village, Buleleng Regency, Bali.Keywords : Quality of Service, Homestay, Satisfaction